2008
DOI: 10.1097/shk.0b013e31816a6bb1
|View full text |Cite
|
Sign up to set email alerts
|

NEUTROPHIL-DERIVED CIRCULATING FREE DNA (cf-DNA/NETs)

Abstract: The release of "neutrophil extracellular traps" (NETs) has been identified as a novel immune response in innate immunity. Neutrophil extracellular traps are composed of neutrophil-derived circulating free DNA (cf-DNA), histones, and neutrophil cytoplasm-derived proteins such as proteases. Here, we studied the putative predictive value of plasma cf-DNA/NETs for the development of sepsis and mortality after multiple trauma. In a prospective pilot study with 45 multiple trauma (Injury Severity Score>16) patients,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
132
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 218 publications
(153 citation statements)
references
References 30 publications
12
132
0
2
Order By: Relevance
“…As we mentioned above, the citrullination of histones, in particular histone H3, is a post‐translational modification that regulates gene expression and plays a critical role in NET development and in inflammatory and host defense response 2, 3, 4, 5, 6. This reaction is catalyzed by PAD4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As we mentioned above, the citrullination of histones, in particular histone H3, is a post‐translational modification that regulates gene expression and plays a critical role in NET development and in inflammatory and host defense response 2, 3, 4, 5, 6. This reaction is catalyzed by PAD4.…”
Section: Discussionmentioning
confidence: 99%
“…Citrullination of histones, in particular histone H3, is one of the major points for inflammatory signals that trigger the neutrophil response to infections 2, 3, 4, 5. Nevertheless, citrullinated histone H3 is also important in the development of neutrophils extracellular traps (NETs) 5, 6. It has been reported that elevated levels of NETs in the plasma may predict multiple organ dysfunction and sepsis in trauma patients 6…”
Section: Introductionmentioning
confidence: 99%
“…After the addition of EDTA (5 m M ) to prevent further MNase activity, the samples were centrifuged and the supernatants were collected. The DNA concentration in the PMN supernatants and the cf-DNA in the plasma samples were determined using SYBR® Gold Nucleic Acid Gel Stain (Invitrogen, Carlsbad, Calif., USA) staining as previously reported [15]. Fluorescence intensity reflects the amount of DNA and was measured using a microplate reader (VICTOR 3 ; USA).…”
Section: Methodsmentioning
confidence: 99%
“…NET induce platelet adhesion, activation, and aggregation that finally promote fibrin deposition, indicating that NET are a link between inflammation and thrombosis [14]. In patients with sepsis, there is an increase in the level of circulating free DNA (cf-DNA) in peripheral blood [15], which has been considered a marker for NETosis.…”
Section: Introductionmentioning
confidence: 99%
“…NET formation depends on generation of reactive oxygen species, and consequently patients with NADPH oxidase deficiency (chronic granulomatous disease) exhibit a deficiency in NET formation that may further contribute to their predisposition to severe and chronic infections. The presence and kinetics of free circulating neutrophilderived DNA/NETs appear to serve as a useful marker of sepsis disease severity and multiple organ failure in patients following multiple traumas [84]. Specific bacterial products, such as the surface expressed M protein of S. pyogenes, or host chemokines, such as IL-8, can induce the production of NETs [85,86].…”
Section: Induction Of Neutrophil Extracellular Trap-associated Cell Dmentioning
confidence: 99%